Retention of Knowledge in Preclinical Disciplines by Clinical Students in the IIUM Medical Programme - Hasan, Taufiq Hidayat; Muhammad, Siti Aeshah @ Naznin; Abdullah, Nor Zamzila; Mint, Yi Yi; Aung, Nilar; Jantan, Abdul Wahab (2013)
Introduction: A thorough knowledge in the various disciplines of the basic sciences is a major importance for the practice of clinical medicine. Many basic sciences teachers share a common concern that much of what they teach in preclinical phase is soon forgotten when students move to clinical years. Objective: To examine the retention of such knowledge by clinical students in the Medical Programme of International Islamic University Malaysia (IIUM). Methods: Sixty seven Year 3 and 64 Year 5 students undergoing the Paediatric posting rotation of the academic sessions 2011/2012 were included into this study. Open-ended, short-answer questions of the completion type in the disciplines of anatomy, physiology, biochemistry and general pathology constructed by experts were used. These questions were used to test the retention of the above stated knowledge. Self-administered questionnaire was also designed to obtain the perceptions of students on the learning of basic medical sciences. Results: A significant difference was seen between the mean total scores for the Year 3 and Year 5 students in the basic medical sciences knowledge tests (31.9% vs. 37.7%; p = 0.002). Year 5 students showed significantly higher retention of knowledge on anatomy and biochemistry (p<0.001 and p=0.021). Overall in approximately 50% of the questions students indicated that they knew the answers but could not recall. Seventy percent of students stated that they only attempted to retain facts that they perceived as important. Almost all the students (96.2%) agreed that they remembered information better due to vertical integration in the curriculum. Conclusions: This study did not see deterioration in the retention of knowledge in basic medical sciences as the clinical students progress through clinical years. Students stated that the integration of knowledge in basic medical sciences disciplines into the clinical sciences during the preclinical years helped them remember facts better.